1996
DOI: 10.1007/bf00327730
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Effect of medium composition on the production by a new Bacillus subtilis isolate of protease with promising unhairing activity

Abstract: In a search for microorganisms producing extracellular protease with unhairing activity, Bacillus subtilis IIQDB32 was isolated. Protease formation was significantly stimulated by glucose, tryptone, yeast extract, Ca(2+) and Mn(2+), but was repressed by ammonia and Fe(2+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…It is well known fact that the metal ions in the fermentation medium greatly influence the protease production by microbes (Varela et al 1996). Results revealed that MnCl 2 stimulated the enzyme production (4091 U/gss), followed by FeSO 4 (3855 U/gss), whereas, CuSO 4, ZnSO 4 and CoCl 2 inhibited the production.…”
Section: Discussionmentioning
confidence: 93%
“…It is well known fact that the metal ions in the fermentation medium greatly influence the protease production by microbes (Varela et al 1996). Results revealed that MnCl 2 stimulated the enzyme production (4091 U/gss), followed by FeSO 4 (3855 U/gss), whereas, CuSO 4, ZnSO 4 and CoCl 2 inhibited the production.…”
Section: Discussionmentioning
confidence: 93%
“…Maximum growth (2.14 x 10 11 CFU/ml) was observed in cultures using media M4 after 48 h of incubation. Protease synthesis is affected by the presence of easily metabolizable sugars and nitrogen sources in the medium Varela et al, 1996). Presently, no defined medium has been established for the optimum production of alkaline protease from different microbial sources.…”
Section: Effects Of Media Composition On Protease Productionmentioning
confidence: 99%
“…Therefore, the effect of various carbon and nitrogen nutrient cost-effective substrates, divalent metal ions, environmental and fermentation parameters such as pH, temperature, aeration, and agitation were evaluated in the literature (Adinarayana and Ellaiah, 2002;Varela et al, 1996). However, for optimization of all factors and establishment the best possible conditions by considering all interaction of parameters, numerous experiments have to be carried out, which is not economical and practical.…”
Section: Introductionmentioning
confidence: 99%